Digitalis-Like Induced Arrhythmia in a Patient with Rheumatic Mitral Regurgitation Complicated by Preeclampsia - Roscani, Meliza Goi [UNESP]; Zanati, Siimeia G. [UNESP]; Magalhaes, Claudia G. [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Informa Healthcare, 2010)
Objective. To report a case of cardiac arrhythmia related to a low dose of endovenous lanatoside C. Case report. A 23-year-old pregnant woman with mitral regurgitation complicated with preeclampsia and pulmonary edema presented 2 episodes of atrial tachycardia induced by a intravenous digitalis (2 mg, IV and 1 mg, IV, respectively). Conclusion. This case calls attention to the need for further studies analysing the security of digoxin use in preeclampsia.</.